The 1917-th Year Russian Revolution and its Reflection in the Rare Editions of the Library of Russian Academy of Sciences - Galina Nikolaevna Pitulko; Alexey Petrovich Isaev (Управленческое консультирование)
In this article we are talking about the 1917-th year Russian revolution rare editions, which are stored in the Library of the Russian Academy of sciences. There are some examples of the most interesting rare editions. The authors consider this theme on the basis of book collection of the scientific department of the rare books of the Library of Russian Academy of Sciences.